Effects of hypertonic alkaline nasal irrigation on COVID‐19. Issue 6 (19th November 2021) - Yilmaz, Yetkin Zeki; Yilmaz, Begum Bahar; Ozdemir, Yusuf Emre; Kocazeybek, Bekir Sami; Karaali, Ridvan; Çakan, Doğan; Ozdogan, Hasan Ahmet; Batioglu‐Karaaltin, Aysegul
Abstract: Objective: The causative agent of COVID‐19 is a novel member of coronaviridaes, SARS‐CoV‐2. It has been reported that the spike (S) protein of SARS‐CoV‐2 is responsible of infectivity. The S protein is demonstrated to be inactivated under environmental condition, such as hypertonicity and alkaline pH. The aim of the study was to investigate the effect of hypertonic alkaline nasal irrigation (HANI) on SARS‐CoV‐2. Methods: Sixty patients divided into two groups. The patients in Group 1 used hydroxychloroquine (HCQ), and the patients in Group 2 used HCQ and HANI. Nasopharyngeal samples were collected at the beginning, on 3rd and 7th day of the PCR test positivity. The nasopharyngeal viral load (NVL) changes analyzed with quantitative PCR. Results: NVL decrease in weekly period was statistically significant for both groups, when the difference between NVL day 0 and 3rd in Group 1 and NVL difference between day 0 and 3rd in Group 2 were compared. The difference between Groups 1 and 2 in terms of NVL change was statistically significant ( P  < 0.05). Conclusion: We demonstrated a significant decrease in nasopharyngeal SARS‐CoV‐2 load with HANI solution and suggest that HANI may be promising modality for the COVID‐19 treatment. Level of evidence: IB